Restoration of Global Offset and Limb Length in Primary Unilateral Total Hip Arthroplasty When Preoperative Templating is not Applied - Kamal, Miran Twana; Saeed, Arewan Mohammed Salih; Mahmud, Kawa Abdullah (Sulaimani Journal for Pure and Applied Sciences, 2022)
Background: Preoperative templating is an essential step before performing any total hip arthroplasty (THA). Restoration of global offset (GO) and limb length (LL) were among the templating purposes. Thus, we aimed to perform THA without preoperative templating based on clinical examination and intra-operative anatomical landmarks to restore hip biomechanics. Patients and methods: This prospective observational study was conducted on 40 patients with primary THA through the posterior approach. The lesser trochanter was used to determine the level of femoral neck cut, the femoral component insertion depth, and version, along with adjusting the level of the center of the femoral head to the tip of the greater trochanter. The transverse acetabular ligament (TAL) was used as a reference for the acetabular component version and inclination. To optimize the LL, preoperative clinical assessment, intra-operative comparison with the normal side, soft tissue tension, and shuck test were used. GO was adjusted using the depth of acetabulum after reaming, placing the acetabular component fit or 10% overhang from the ridge and gluteus medius muscle tension. Postoperatively, computed tomography (CT) scan was used for measuring the GO (acetabular offset (AO) + femoral offset (FO)) and limb length discrepancy (LLD) and compared to the sound side. Pre and postoperatively, LL was measured using a tape measure from the anterior superior iliac spine (ASIS) to the medial malleolus. Results: Depending on postoperative CT measurements, there was no significant difference between the mean normal and operative GO (P=0.894). The mean LL difference between the two sides was 0.38 cm (P=0.007). Clinically, the mean LLD (comparing the normal side with the operated side preoperatively) was 1.001 cm, while the mean LLD was 0.722 cm (P=0.0455). Conclusions: This study demonstrated that when the preoperative templating step is omitted, depending on intraoperative landmarks, neither the GO nor the AO and FO of the operated side were significantly affected. The mean radiological and clinical postoperative LLD was almost consistent, and the mean difference was < 1 cm, which is within the acceptable range. Do not use abbreviations in abstract and conclusions.
Keywords: Total hip arthroplasty; Preoperative templating; Global offset; Limb length discrepancy